Yogurt.The most suitable carrier for increasing bioavailability of minerals - Hashemi Gahruie, Hadi (Progress in Nutrition, 2018)
The aim of this paper is to highlight that the incidence of essential micronutrients deficiency is worldwide. Different foods maybe used as a matrix for mineral fortification and enrichment purposes; however, most of them suffer from low bioavailability. Because of appropriate physicochemical and microbial properties such as acidity, inhibitory effect on phytic acid as well as having probiotics and vitamins, yogurt is the best carrier for increasing the bioavailability of mineral.